2015
DOI: 10.1080/10803548.2015.1096063
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of work-related musculoskeletal disorders among male kitchen workers in South India

Abstract: The male kitchen workers who participated in this research were found to possess both MSDs and ergonomic hazards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 20 publications
6
27
2
Order By: Relevance
“…[37,38] In this study, it is observed that workers among 15-30 years age group are found less affected from WMSDs compared to higher age groups of workers. It is interesting to observe that workers with higher education levels (secondary and tertiary) are …”
Section: Discussionmentioning
confidence: 58%
“…[37,38] In this study, it is observed that workers among 15-30 years age group are found less affected from WMSDs compared to higher age groups of workers. It is interesting to observe that workers with higher education levels (secondary and tertiary) are …”
Section: Discussionmentioning
confidence: 58%
“…The highest prevalence rate of MSD is for the lower back (65.8%), shoulder region (62.3%) and followed by finger/ wrist (43.9%), knee/foot (42.1%), neck region (38.6%), elbow/forearm (31.6%), thigh (30.7%), upper back (21.1%), and chest (20.2%), respectively as shown in the Figure 1. On the other hand, the study results infer that Indian flatbread preparation is a more risky task than the other tasks like preparation of dosa and preparation of rice in the case of Indian kitchen work [13,14]. The findings have served the grounds for assessing the muscle activity on the low back and shoulder region among institutional kitchen workers in south India during their various tasks such as Indian flatbread (chapati) preparation.…”
Section: Introductionmentioning
confidence: 77%
“…Our previous studies on kitchen workers are in line with several findings. It has been stated that the result of the Nordic Musculoskeletal Questionnaire (NMQ) survey among 114 male kitchen workers indicates 67.5% of MSDs during the past 12 months [13,14]. The highest prevalence rate of MSD is for the lower back (65.8%), shoulder region (62.3%) and followed by finger/ wrist (43.9%), knee/foot (42.1%), neck region (38.6%), elbow/forearm (31.6%), thigh (30.7%), upper back (21.1%), and chest (20.2%), respectively as shown in the Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Singh y Chokhandre (2015) [289] India Application of the NMQ in garbage collectors. Subramaniam y Murugesan (2015) [290] India Application of the NMQ in kitchen workers. Lourenco et al (2015) [291] Portugal Application of the NMQ in workers under 21 years of age.…”
Section: Authors Location Observationsmentioning
confidence: 99%
“…Shankar et al [288] as well as Subramaniam and Murugesan [290] studied MSD in kitchen workers. The data were gathered with the NMQ and direct observation.…”
Section: Othersmentioning
confidence: 99%